Modern strategies for study of tumor’s markers in clinical practic - I. B. Zborovskaya (Успехи молекулярной онкологии)
Importance of molecular genetics-based essays in clinical oncology is now unquestionable due to the fact that all oncological diseases and their progression are based on cascading accumulation of genetic aberrations involving more than 20 different genes. Essentially new capacities of clinical oncology are uncovered with the help of modern molecular biology methods that allow to determine structural and functional changes of genes and their products. This review examines approaches to improve criteria for creating diagnostic essays, evaluation of treatment efficiency and molecular factors of clinical course. In order to determine relevant markers, special consideration should be given to the research of signal transduction pathways involving key genes responsible for tumor growth and their partners. The correct formation of patient’s groups and selection of samples is very important. It is emphasized that integrated clinical programs should combine traditional methods of diagnostics and treatment with modern molecular testing and bioinformatics methods.